Bio-efficacy of flumioxazin in soybean (Glyceine max) - BILLORE, S D; VYAS, A K; JOSHI, O P; PANDYA, N; KHAN, I R (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during rainy seasons of 2004 and 2005 to study the effectiveness of flumioxazin 50% WP against weeds of soybean (G[ycirze tnax (L.) Merr.). Results revealed that the application of flumioxazin @ 45 g/ha ha as pre-emergence in soybean effectively contain the weed load, promotes growth of soybean leading to enhanced yield. The physical optimum level of flumioxazin as pre-emergence was found to be 36.19 g/ha for achieving the maximum yield (2 050 kg/ha) and weed control. The dicot weed control efficiency of flumioxazin was found to be higher than trifluralin at all the stages of observations.